Mathematics in the Real World - Wallis, W.D. (Springer New York : Imprint: Birkhũser, 2013)
Mathematics in the Real World is a self-contained, accessible introduction to the world of mathematics for non-technical majors. With a focus on everyday applications and context, the topics in this textbook build in difficulty and are presented sequentially, starting with a brief review of sets and numbers followed by an introduction to elementary statistics, models, and graph theory. Data and identification numbers are then covered, providing the pathway to voting and finance. Each subject is covered in a concise and clear fashion through the use of real-world applications and the introduction of relevant terminology. Many sample problems <U+0013> both writing exercises and multiple-choice questions <U+0013> are included to help develop students<U+0019> level of understanding and to offer a variety of options to instructors. Covering six major units and outlining a one-semester course, Mathematics in the Real World is aimed at undergraduate liberal art students fulfilling the mathematics requirement in their degree program. This introductory text will be an excellent resource for such courses, and will show students where mathematics arises in their everyday lives.